ANALISIS PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP TINGKAT KEPATUHAN PENGUNGKAPAN KONVERGENSI IFRS PADA LAPORAN LABA RUGI KOMPREHENSIF - Pitasari, Anggita; Septiani, Aditya (Diponegoro Journal of Accounting, 2014)
This study aims to analyseÂ  how corporate governance structures affect the level of disclosure compliance convergence of IFRS in statements of comprehensive income. This research is the development of a study conducted by Al Akra et al . (2010) and Prawinandi et al . (2012) .Data analysis method used is descriptive analysis method and hypothesis testing . Tests performed using SPSS release 16. Overall sample of 40 service companies used in this study.The results of this study showed that the average level of disclosure compliance convergence of IFRS in statements of comprehensive income is 50.61 %. The results of multiple regression analysis showed that the structure of corporate governance which affect the level of disclosure compliance convergence of IFRS in statements of comprehensive income is the number of audit committee members and the number of audit committee meetings. Meanwhile, a variable number of commissioners, the proportion of independent commissioners, the number of commissioners meeting, leverage, liquidity, and profitability are not significantly influence with the level of disclosure compliance convergence of IFRS in statements of comprehensive income.